Growth and characterization of halogen substitution in counter benzenesulfonate of organic nonlinear optical crystal : DASB - Fei You; Fei Teng; Chen Huang; Zhe Yu; Dong Chen; Lihua Xia; Lifeng Cao; Bing Teng (Materials Research Express, 2020)
The organic stilbazolium derivative crystal4-dimethylamino-N′-methyl-4′- stilbazolium p- bromobenzenesulfonate (DASB) was successfully grown by spontaneous nucleation method coupled slow evaporation (SNM-SE) for the first time. The corresponding powder XRD revealed the crystalline nature of the DASB material, and various functional groups were determined by FT-IR. The thermal stability and melting point were analyzed by TG/DTG and DSC measurement. The absorption coefficient, band gap energy, cut-off wavelength and extinction coefficient were obtained through UV–vis-NIR spectral study. Photoluminescence result indicates DASB crystal exists purple emission at 405 nm and 467 nm because of the π – π * and defect transitions, respectively. The SHG efficiency of DASB crystal is about 3 times higher than KDP crystal. All the encouraging results indicate the DASB crystal is a promising candidate for the Thz generation applications.